Perceptions of Self-Efficacy and Perceived Benefits in Adolescents About Covid-19 Vaccine in the Working Area of Telaga Dewa Health Center, Bengkulu City - Hijratul Ullia; Wisuda Andeka Marleni; Reka Lagora Marsofely (Indonesian Journal of Health Research and Development, 2023)
SARS-COV-2 is the virus that causes Corona Virus Disease-19, an infectious disease. As of April 17, 2022, Bengkulu, one of the corona virus-infected provinces, has 29,099 confirmed cases and 167 fatalities. The new goal of 52% of 2,215 youth has not been met in terms of youth vaccination rates. The study's objective was to examine how adolescents in Bengkulu City's Telaga Dewa Health Center worked with the Covid-19 vaccine. In-depth interviews with theory of the health belief model and focus group discussion approaches are two of the qualitative methods used in this study to get information. The results are given as descriptive data that has been prepared verbally based on the outcomes of in-depth interviews with informants. Teenagers (15–17 years old) who were divided into 5 groups 5 who had received vaccinations and 5 who had not as well as 2 support groups consisting of parents of teenagers and Covid-19 vaccine professionals served as the study's informants. In order to implement the health belief model, this study collected data from a group of adolescents who had received vaccinations and those who had not. It was discovered that the adolescents had a positive perception of their vulnerability, were aware of the seriousness of the Covid-19 virus which can be fatal and the advantages of the Covid-19 vaccine. However, based on the experiences of those closest to them, the adolescents were still unclear about the vaccine's side effects. Adolescent immunization rates should be increased, according to recommendations.